ANALISIS PENETAPAN KRITERIA KAWASAN HUTAN - Zulkarnain, Zulkarnain (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
The purpose of this analysis is to determine ( 1 ) What are the criteria based on the forest slope , soil type and rainfall can be used as a basis for determining the hedging function , functional conservation and production functions , and ( 2 ) the criteria to meet the balance of forest ecosystems in the created in the layout plan of the province.The research was conducted for 4 ( four ) months from December 2012 to April 2013 , at the Faculty of Agriculture University GIS Laboratory Mulawarman , and several government agencies East Kalimantan Province .Data collection is done by : ( 1 ) data collection library , ( 2 ) data collection of government policy , and ( 3 ) observation satellite map.This research used descriptive analysis method by comparing the criteria with the forest setting policy rules of the forest ecosystem and forest conditions in the field that have a negative impact on the environment . Data from the analysis of Landsat satellite imagery from the comparator would be a real forest conditions , and generally explore the benefits and functions of the forest as is .The results showed that : ( 1 ) setting the criteria forest slope , soil type , and rainfall can not be made the basis of the criteria in determining the area of protected forests , forest conservation and forest production , and ( 2 ) the main criteria that can be used the setting is the availability of forest trees count as forming community forest.